2018
DOI: 10.1007/s11814-018-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of naphthalene adsorption on activated carbons prepared from different raws

Abstract: Five activated carbons (ACs) from apricot shells (ACAS), mixture of lignin and cellulose (ACLC), wood (ACW), walnut shells (ACWS), and coal (CAC) were prepared and used as adsorbents to study the adsorption behavior of naphthalene. All ACs were characterized by scanning electron microscopy, N 2 adsorption-desorption method, Xray photoelectron spectroscopy, and elemental analysis. The effects of initial concentration, contact time, ionic strength, pH, and temperature on the adsorption of ACs for naphthalene we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…It was found that disubstituted phenolic derivatives were adsorbed in larger amounts than monosubstituted derivatives. It was determined that the maximum sorption capacities made up 101.7 to 533.25 mg/g [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was found that disubstituted phenolic derivatives were adsorbed in larger amounts than monosubstituted derivatives. It was determined that the maximum sorption capacities made up 101.7 to 533.25 mg/g [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…in an aqueous solution at room temperature depends on the texture and chemical properties of the ACs [12]. Liu et al also pointed out that the adsorption of naphthalene using ACs prepared by a variety of biomass depends on the same properties, which are the elemental composition and surface functional groups [13]. In view of the above, both physical adsorption and chemical adsorption may contribute to naphthalene adsorption on ACs.…”
Section: Cabal Et Al Reported That the Adsorption Of Naphthalene By Acsmentioning
confidence: 99%
“…Выявлено, что АУ, полученный из отходов переработки абрикоса, имеет малую удельную поверхность и, соответственно, самое низкое значение максимальной сорбционной емкости (175.44 мг/г) из исследованных образцов углей [97]. Определено, что все изотермы адсорбции более точно описываются моделью Фрейндлиха, а кинетика процесса -моделью псевдо-второго порядка.…”
Section: нефть и нефтепродуктыunclassified